Finite element analysis on post-buckling of thin-walled structures using ANSYS - Kong Kah Hon Danny. (2009)
This project studies the feasibility of applying finite element analysis (FEA) to simulate the buckling and post-buckling behaviours of cold-formed thin-walled steel structures, thereby predicting their ultimate load bearing capability in axial compression. ANSYS, a commercial finite element software, was used in this study. This report documents the improvements made on the design procedure for ultimate load prediction, with the aim of obtaining load results which are accurate, robust and conservative for real-time utilisation.